Medical and family caregivers' conceptions in the face of advance directives - Silvana Bastos Cogo; Marcio Rossato Badke; Luiza Carolina Santos Malheiros; Daiana de Araújo; Aline Gomes Ilha (Universidade Federal de Santa Maria, 2019)
Objective: To understand how doctors and family caregivers understand the applicability of the Advance Directives to end-of-life care. Method: qualitative, descriptive and exploratory research, conducted with seven doctors of a university hospital in southern Brazil and seven family caregivers of patients at the end-of-life, from October to December 2014, from semi-structured interviews, submitted to discursive textual analysis. Results: two categories emerged: Advance Directives: the right to personal autonomy and conflicts and dilemmas in the applicability of Advance Directives. Conclusion: The Advance Directives are related to the respect of personal autonomy, professional support and reduction of the anguish and suffering of family care in view of the decision-making processes that involve the end of life. However, it is a practice surrounded by fears and concerns about its applicability and compliance by the professional.